Analysis of the behavior of moored tankers - P. Costa (2008)
Moored ship behavior inside harbors and, therefore, the operational and security conditions at a port terminal does not have a straightforward relationship with local environmental conditions. Due to the diversity and complexity of the phenomena involved it is important to use a methodology that combines physical model tests with numerical simulations, taking advantage of potential synergies. Results of prototype measurements are also a key element to making the validation and calibration of both physical and numerical models possible. This paper focuses on studying the behavior of moored tankers using combined methodology. Aspects related with the inclusion in the numerical models of shallow water effects, non-linear characteristics of mooring lines and fenders, the influence of harbor boundaries and viscous damping are analyzed and discussed. The role of physical modeling as a tool to address/quantify some of the conditions and to provide data for the calibration of numerical models is presented, as well as the methodology defined for the study of the operational conditions at an existing berth. This methodology includes the development of a computer vision system to measure ship motion at the port terminal (prototype). Actual operational conditions at the berth are also described in the paper.